(3CKQ GdJaGYd Hjf OYGeGJ GdJYde GdHfGFjI h CSdhH GdJYde aj JbOje GdeMJhi GdEdcJQhfj Ydi JfejI GdJMUjd GdeYQaj h GdegGQj ddJUeje GdJYdjej dOi WdGH JcfhdhLjG GdJYdje (B/ s - (3CSeGA UHMj YHOGdMejOs; (3Ced YHOGdaJGM ShjOGf (B: s; (3fGOQ SYjO Tjei (B: s ((3GdbGgQI (B: s (3CSeGA UHMj YHOGdMejO (B: s, 2015)
(3jgOa gPG GdHMK dbjGS CKQ GdJaGYd Hjf OYGeGJ GdJYde GdHfGFjI (B((3HSjW (B{u(32013(B} (3eJhSW (B- (3cKja(B) (3hCSdhH GdJYde (B( (3GdeSJbdjf (B{u(32013(B} (3GdeYJeOjf(B) (3aj JbOje GdeMJhi GdEdcJQhfj Ydi JfejI GdJMUjd GdeYQaj hGdegGQj ddJUeje GdJYdjej dOi WdGH JcfhdhLjG GdJYdje(B: (3hJchfJ YjfI GdHMK ef (B(90) (3WGdH ef WdGH bSe JcfhdhLjG GdJYdje (B{u(32013(B} (3cdjI GdJQHjI GdfhYjI (B{u(32013(B} (3LGeYI Gdajhe; hcTaJ GdfJGFL Yf hLhO aQhb OGdI EMUGFjkG Hjf eJhSWGJ OQLGJ cd ef GdWdGH GdPjf OQShG GdeMJhi GdEdcJQhfj HOYGeGJ GdJYde GdHSjWI(B: (3hGdWdGH GdPjf OQShG GdeMJhi GdEdcJQhfj HOYGeGJ GdJYde GdeJhSWI(B: (3hGdWdGH GdPjf OQShG GdeMJhi GdEdcJQhfj HOYGeGJ GdJYde GdcKjaI(B: (3aj GdJMUjd GdHYOj GdeYQaj hGdegGQj(B: (3hcPdc hLhO aQhb OGdI EMUGFjkG Hjf eJhSWGJ OQLGJ cd ef GdWdGH GdeSJbdjf Yf GdeLGd GdEOQGcj(B: (3hGdWdGH GdeYJeOjf Ydi GdeLGd GdEOQGcj aj GdJMUjd GdeYQaj hGdegGQj aj GdJWHjb GdHYOj(B: (3dUGdM eLehYI GdeSJbdjf Yf GdeLGd GdEOQGcj(B: (3hhLhO aQhb OGdI EMUGFjkG Hjf eJhSWGJ OQLGJ GdWdGH aj GdJMUjd GdeYQaj hGdegGQj GdHYOj, JQLY Edi CKQ GdJaGYd Hjf eSJhjGJ OYGeGJ GdJYde (B((3GdHSjW (B{u(32013(B} (3GdeJhSW (B{u(32013(B} (3GdcKja(B)(3, hCSdhH GdJYde (B-(3GdeSJbdjf (B{u(32013(B} (3GdeYJeOjfs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe JcfhdhLjG GdJYdjes
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdeSJbdjf Yf GdeLGd GdEOQGcjs; (3OYGeGJ GdJYde GdHfGFjIs; (3eSJhjGJ JbOje OYGeGJ GdJYdes